Synchronous measurement of the normal ground reaction force on shoe spikes and forceplate - Hossain, Z.; Grill, J.; Grill, W.; MacIntosh, B. (ISBS Proceedings Archive (Michigan), 2017)
Monitoring balance and ground reaction forces (GRFs) during movement has obvious advantages. Sensor spikes (SS) can measure vertical GRFs while standing, walking, jogging, running, and jumping and compared with Kistler force plate. All the data from SS are derived from the time dependent voltage variations of piezo spikes, which are observed with the aid of a computer controlled transient recorder. The measurement was obtained from SS placed under the heel and forefoot. Monitoring is performed on 12 healthy subjects 29 ± 3 years of age. The force resolution is ± 0.25 N and temporal resolution is ± 0.01 ms. The contact time, take off time, impact force, active force phases of heel and forefoot have been monitored and quantified. The system is compact, battery driven and allows monitoring of the on-field GRFs during athletic and general activities.